The Intrauterine and Nursing Period Is a Window of Susceptibility for Development of Obesity and Intestinal Tumorigenesis by a High Fat Diet in Min/+ Mice as Adults - Ha Thi Ngo; Ragna Bogen Hetland; Inger-Lise Steffensen (Journal of Obesity)
We studied how obesogenic conditions during various life periods affected obesity and intestinal tumorigenesis in adult C57BL/6J-Min (multiple intestinal neoplasia)/+ mice. The mice were given a 10% fat diet throughout life (negative control) or a 45% fat diet in utero, during nursing, during both in utero and nursing, during adult life, or during their whole life-span, and terminated at 11 weeks for tumorigenesis (Min/+) or 23 weeks for obesogenic effect (wild-type). Body weight at 11 weeks was increased after a 45% fat diet during nursing, during both in utero and nursing, and throughout life, but had normalized at 23 weeks. In the glucose tolerance test, the early exposure to a 45% fat diet in utero, during nursing, or during both in utero and nursing, did not affect blood glucose, whereas a 45% fat diet given to adults or throughout life did. However, a 45% fat diet during nursing or during in utero and nursing increased the number of small intestinal tumors. So did exposures to a 45% fat diet in adult life or throughout life, but without increasing the tumor numbers further. The intrauterine and nursing period is a window of susceptibility for dietary fat-induced obesity and intestinal tumor development.